Investigating The Underlying Components in Business Incubation Process in Malaysian ICT Incubators - Abdul Khalid, Fararishah (Leena and Luna International, 2012)
The role of business incubators as an economic development tool has been reiterated in the entrepreneurship literature. Business incubators have been proven as effective in creating jobs, and accelerating the growth of new businesses. Both developed and developing countries have taken the business incubation route to encourage the spur of small to medium sized enterprises. Although the basic concept of business incubation remains until today, there have been several enhancements to the capability of business incubators as an economic driver. Malaysia is an example of a developing nation that has implemented its business incubation programmes in its effort to generate a critical mass of technology-based entrepreneurs.This paper examines the underlying components in the business incubation process in the Malaysian ICT incubators. A survey questionnaire method was used to solicit response from 118 incubatees from 15 ICT incubators in Malaysia. Exploratory factor analysis was performed to identify the underlying components. Results suggest that there are eleven components in the business incubation process.